2017
DOI: 10.1177/0013916517706730
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Compensatory Beliefs in Rationalizing Environmentally Detrimental Behaviors

Abstract: Compensatory green beliefs (CGBs) reflect the idea that a pro-environmental behavior (e.g., recycling) can off-set the negative effects of an environmentally detrimental behavior (e.g., driving). It is thought that CGBs might help explain why people act in ways that appear to contradict their pro-environmental intentions, and inconsistently engage in pro-environmental behaviors. The present study sought to investigate the nature and use of CGBs. A series of interviews suggested that participants endorsed CGBs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 46 publications
2
41
0
2
Order By: Relevance
“…The current research also adds to research showing that people are not always consistent when it comes to their environmentally friendly behaviors across situations and time (e.g., Hope et al, 2017;Meijers, Noordewier, & Avramova, 2013;Nilsson, Bergquist, & Schultz, 2017;Truelove, Carrico, Weber, Raimi, & Vandenbergh, 2014). That is, on one hand, research shows that one's environmentally friendly behavior in one domain may positively spill over into another domain.…”
Section: Sustained Environmentally Friendly Behaviorsmentioning
confidence: 54%
See 1 more Smart Citation
“…The current research also adds to research showing that people are not always consistent when it comes to their environmentally friendly behaviors across situations and time (e.g., Hope et al, 2017;Meijers, Noordewier, & Avramova, 2013;Nilsson, Bergquist, & Schultz, 2017;Truelove, Carrico, Weber, Raimi, & Vandenbergh, 2014). That is, on one hand, research shows that one's environmentally friendly behavior in one domain may positively spill over into another domain.…”
Section: Sustained Environmentally Friendly Behaviorsmentioning
confidence: 54%
“…People tend to retrieve and present information in such a way that it helps them to justify their behaviors and see themselves in a positive light. For example, when people feel conflicted about their environmental behaviors, they think of previous environmentally friendly behaviors to make themselves feel better (Hope, Jones, Webb, Watson, & Kaklamanou, 2017). The research on self-servingness may explain why people show vicarious licensing effects; that is, because of the moral behaviors of close others, they may feel licensed to behave in a more morally questionable manner while being able to see these transgressions in a more positive light due to the moral behaviors of close others.…”
Section: Vicarious Licensing But Not Cleansingmentioning
confidence: 99%
“…Such a stance is congruent with a consumer typology identified as "light greens" [48]; this group may be responding to extrinsic demands to adopt green behaviours. In contrast people who embrace the NEP and reject the DSP may have internalised the need to think and behave in a pro-environmental manner, which fits with a committed environmentalist or "deep green" typology [49][50][51]. Interestingly, a belief in the scientific tradition and a conviction that science and technology can solve environmental problems within current political structures has been suggested to be a tenet of 'environmentalism' in contrast to 'ecologists' who reject science [52].…”
Section: Dimensionality Of the Nep Scalementioning
confidence: 99%
“…guilt) towards negative environmental behaviour. This in turn made them feel more positive about their overall environmental impact (Hope et al, 2017). These findings indicate that CBGs are sometimes used to justify a person's environmentally damaging behaviour.…”
Section: Moral Licencing and Compensatory Green Beliefsmentioning
confidence: 77%
“…purchasing organic food as a compensation for flying abroad on holidays (Gregory-Smith, et al, 2013;Kaklamanou et al, 2013). In a qualitative study Hope et al (2017) found that people experienced psychological benefits from holding CGBs as it reduced their negative feeling (e.g. guilt) towards negative environmental behaviour.…”
Section: Moral Licencing and Compensatory Green Beliefsmentioning
confidence: 99%